Assessment of the Effect of Fungicide and Seed Rate on the Incidence of Leaf Blast (Magnaphorthe Grisea), On the Growth of Foxtail Millet (Setaria Italica (L.) P. BEAUV) in North-eastern Nigeria - Turaki , Z. G. S; Richard , B. I; Degri, M. M. (Asian Journal of Agriculture and Rural Development, 2014)
In 2007 a multilocational trial was conducted in a split-plot using randomized complete block University of Maiduguri and Gashua Farm station to assess the effects of fungicide and seed rate on the incidence of leaf blast (Magnaphorte grisea), on the growth and yield of foxtail millet in the Northeastern Nigeria. The results showed that the lowest disease incidence of 20.8% and 0.4% were recorded from 100% recorded significantly (P < 0.05) the highest disease incidence of 80.0% and 64.3% at Maiduguri and Gashua respectively. The highest plant height and panicle length were recorded from plants grown at fungicide seed treatment ranging from 80-100% at seed rate of 5.0kg/ha. The lowest plant height and panicle length were obtained from plants grown from the untreated seed tate of 12.5kg/ha and while the lowest grain yields were recorded from untreated seed rate of 5.0kg/h at Maiduguri and Gashua respectively.